Pleasurable music activates cerebral µ-opioid receptors: a combined PET-fMRI study. - Putkinen, Vesa; Seppälä, Kerttu; Harju, Harri; Hirvonen, Jussi; Karlsson, Henry K.; Nummenmaa, Lauri (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: The μ-opioid receptor (MOR) system mediates incentive motivation and the hedonic component of primary rewards such as food and sex. However, there is no direct in vivo evidence for the involvement of the MOR system in pleasure derived from aesthetic rewards such as music. Methods: We measured MOR availability with positron emission tomography (PET) and the agonist radioligand [11C]carfentanil with high affinity for MORs during the listening of pleasurable music and neutral baseline condition. Haemodynamic responses associated with dynamic pleasure ratings during listening to music and control stimuli were measured using functional magnetic resonance imaging (fMRI). Results: The PET results revealed that pleasurable music increased [11C]carfentanil binding in several cortical and subcortical regions, including ventral striatum and orbitofrontal cortex, known to contain "hedonic hotspots". [11C]carfentanil binding in the nucleus accumbens during the music condition was associated with number of pleasurable chills, linking the subjective experience of pleasure to striatal opioid release. Individual variation in baseline MOR tone influenced pleasure-dependent haemodynamic responses during music listening in regions associated with interoceptive, sensorimotor, and reward processing. Conclusions: These findings provide the first neuroimaging evidence that pleasurable music modulates MOR system function. The results indicate that the μ-opioid system governs complex aesthetic rewards in addition to biologically essential primary rewards.